Steps involved in activation of the pro-matrix metalloproteinase 9 (progelatinase B)-tissue inhibitor of metalloproteinases-1 complex by 4-aminophenylmercuric acetate and proteinases. - Ogata, Y; Itoh, Y; Nagase, H (1995)
The precursor of matrix metalloproteinase 9 (pro-MMP-9, progelatinase B) noncovalently binds to tissue inhibitor of metalloproteinases (TIMP)-1 through the C-terminal domain of each molecule. We have isolated the proMMP-9.TIMP-1 complex from the medium of human fibrosarcoma HT-1080 cells and investigated the activation processes of the complex by 4-aminophenylmercuric acetate, trypsin, and matrix metalloproteinase 3 (MMP-3, stromelysin 1). The treatment of the proMMP-9.TIMP-1 complex with 4-aminophenylmercuric acetate or trypsin converts proMMP-9 to lower molecular weight species corresponding to active forms, but no gelatinolytic activity is detected. The lack of enzymic activity results from binding of TIMP-1 to the activated MMP-9. The treatment of the proMMP-9.TIMP-1 complex with a possible physiological proMMP-9 activator, MMP-3, does not reveal any gelatinolytic activity unless the molar ratio of MMP-3 to the complex exceeds 1. This is due to the inhibition of MMP-3 by TIMP-1 forming a ternary proMMP-9.TIMP-1.MMP-3 complex. The formation of the ternary complex weakens the interaction between proMMP-9 and TIMP-1, resulting in partial dissociation of the complex into proMMP-9 and the TIMP-1.MMP-3 complex. When MMP-3 is in excess, the propeptide is completely processed, and the full activity of MMP-9 is detected. Similarly, the proMMP-9.TIMP-1 complex inhibits MMP-1 (interstitial collagenase) and in turn renders the proMMP-9 activable by a catalytic amount of MMP-3. These results suggest that formation of the proMMP-9.TIMP-1 complex regulates extracellular matrix breakdown in tissue by switching the predominant MMP activity from one type to another.